2018
DOI: 10.1016/j.compfluid.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and numerical analysis of unsteady fractional viscoelastic flows in simple geometries

Abstract: In this work we discuss the connection between classical and fractional viscoelastic Maxwell models, presenting the basic theory supporting these constitutive equations, and establishing some background on the admissibility of the fractional Maxwell model. We then develop a numerical method for the solution of two coupled fractional differential equations (one for the velocity and the other for the stress), that appear in the pure tangential annular flow of fractional viscoelastic fluids. The numerical method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 70 publications
0
13
0
1
Order By: Relevance
“…In order to achieve a closed system of equations, a constitutive equation for the extrastress tensor, σ, is required. Recently, Ferrás et al [27] proposed a new differential model based on the Phan-Thien-Tanner constitutive equation [26] (see also [28]). This new model considers a more general function for the rate of destruction of junctions, the Mittag-Leffler function, where one or two fitting parameters are included, in order to achieve additional fitting flexibility.…”
Section: Governing Equationsmentioning
confidence: 99%
“…In order to achieve a closed system of equations, a constitutive equation for the extrastress tensor, σ, is required. Recently, Ferrás et al [27] proposed a new differential model based on the Phan-Thien-Tanner constitutive equation [26] (see also [28]). This new model considers a more general function for the rate of destruction of junctions, the Mittag-Leffler function, where one or two fitting parameters are included, in order to achieve additional fitting flexibility.…”
Section: Governing Equationsmentioning
confidence: 99%
“…19 To be more precise, consider the spatial cylindrical domain governing the -component of the fluid velocity u (r, t). In Ferras et al, 20 the authors proposed a fractional order model governing the fluid velocity u (r, t) :…”
Section: Application To the Taylor-couette Flowmentioning
confidence: 99%
“…In Refs. [11,12,17], the beneficial fitting qualities of this constitutive model framework are discussed in detail. Here, we are interested in determining to what extent the properties of the Mittag-Leffler function can be used to improve the fitting quality of differential models, and this will be discussed in the next subsection.…”
Section: Riemann-liouville and Caputo Fractional Derivativesmentioning
confidence: 99%
“…The model was derived from a Lodge-Yamamoto type of network theory for polymeric fluids, in which the network junctions are not assumed to move strictly as points of the continuum but instead they are allowed a certain effective slip as well as a rate of destruction that depends on the state of stress in the network. Phan-Thien proposed that an exponential function form would be quite adequate to represent the rate of destruction of junctions and in [17] it was shown that the Mittag-Leffler function could improve the quality of model fits to real data by allowing different forms for the rates of destruction.…”
Section: Generalized Phan-thien and Tanner Modelmentioning
confidence: 99%